Proctitis 1 Week after Stereotactic Body Radiation Therapy for Prostate Cancer: Implications for Clinical Trial Design - Paydar, Ima; Cyr, Robyn A.; Yung, Thomas M.; Lei, Siyuan; Collins, Brian Timothy; Chen, Leonard N.; Suy, Simeng; Dritschilo, Anatoly; Lynch, John H.; Collins, Sean P. (Frontiers in Oncology, 2016)
Background Proctitis following prostate cancer radiation therapy is a primary determinant of quality of life (QOL). While previous studies have assessed acute rectal morbidity at 1 month after stereotactic body radiotherapy (SBRT), little data exist on the prevalence and severity of rectal morbidity within the first week following treatment. This study reports the acute bowel morbidity 1 week following prostate SBRT. Materials and methods Between May 2013 and August 2014, 103 patients with clinically localized prostate cancer were treated with 35–36.25 Gy in five fractions using robotic SBRT delivered on a prospective clinical trial. Bowel toxicity was graded using the Common Terminology Criteria for Adverse Events version 4.0 (CTCAEv.4). Bowel QOL was assessed using the EPIC-26 questionnaire bowel domain at baseline, 1 week, 1 month, and 3 months. Time-dependent changes in bowel symptoms were statistically compared using the Wilcoxon signed-rank test. Clinically significant change was assessed by the minimally important difference (MID) in EPIC score. This was defined as a change of 1/2 standard deviation (SD) from the baseline score. Results One-hundred and three patients with a minimum of 3 months of follow-up were analyzed. The cumulative incidence of acute grade 2 gastrointestinal (GI) toxicity was 23%. There were no acute ≥ grade 3 bowel toxicities. EPIC bowel summary scores maximally declined at 1 week after SBRT (−13.9, p < 0.0001) before returning to baseline at 3 months after SBRT (+0.03, p = 0.94). Prior to treatment, 4.9% of men reported that their bowel bother was a moderate to big problem. This increased to 28.4% (p < 0.0001) 1 week after SBRT and returned to baseline at 3 months after SBRT (0.0%, p = 0.66). Only the bowel summary and bowel bother score declines at 1 week met the MID threshold for clinically significant change. Conclusion The rate and severity of acute proctitis following prostate SBRT peaked at 1 week after treatment and returned to baseline by 3 months. Toxicity assessment at 1 week can therefore minimize recall bias and should aid in the design of future clinical trials focused on accurately capturing and minimizing acute morbidity following SBRT.